Formulasi Kaidah al-Idzhar dan al-Idhmar sebagai Pendekatan Linguistik Al-Qur`an - Firdaus, Yurid Shifan A'lal (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
The process of interpreting the Qur’an requires scientific tools to be able to reveal the meaning contained in each of its verses. One of the tools that must be owned and used is Arabic linguistics in accordance with the language used in the Qur'an. In a series of Qur'anic sentences there is the use of term which are mentioned explicitly sequentially, or mentioned implicitly using pronouns. Such sentence patterns are formulated in the rules of al-iz}ha>r and al-id}ma>r. This article will review the rules of al-iz}ha>r and al-id}ma>r and their existence in the interpretation of the Qur’an. The goal to be achieved through this study is to reveal the implications of the rules of al-iz}ha>r and al-id}ma>r in interpretation as well as displaying the beauty of the systematic language of the Qur’an. The source of this article is literature related to the principles of interpretation and relevant studies so that the research method used in the article is qualitative, descriptive-analytical. After going through the process of description and data analysis, the conclusions obtained are that the rules of al-iz}ha>r and al-id}ma>r can be used as a linguistic approach to the Qur’an to reveal the meaning contained in the systematics of the Arabic language of the Qur’an, whether narrated clearly or stored. The rules of al-iz}ha>r and al-id}ma>r also serve as an argument that the choice of Qur'anic diction contains messages and objectives that can be studied through the rules of language and interpretation in an integrative manner.